Role of Streptococcus mutans two-component systems in antimicrobial peptide resistance in the oral cavity - Miki Kawada-Matsuo; Hitoshi Komatsuzawa (Elsevier, 2017)
Approximately 100 trillion microorganisms exist in the oral cavity. For the commensal bacteria of the oral cavity, it is important to adapt to environmental stimuli, including human- or bacteria-derived antimicrobial agents. Recently, bacterial-specific signal transduction regulatory systems, called two-component systems (TCSs), which appear to be focused on sensing and adapting to the environment, were discovered. Streptococcus mutans is an oral commensal bacteria and is also known as a cariogenic bacteria. Although the virulence factors of S. mutans have been well demonstrated, the mechanism underlying the adaptation of the species to the oral cavity is poorly understood. S. mutans UA159 has 15 sets of TCSs. Among them, several have been demonstrated to be involved in acid tolerance, competence and biofilm formation. Recently, together with our findings, it was demonstrated that 5 TCSs were involved in resistance to antimicrobial agents. Furthermore, another TCS was associated with the production of bacteriocin. Six of 15 TCSs are associated with antimicrobial agents, implying that S. mutans can survive in the oral cavity by resisting various antimicrobial peptides. In this review, we highlight the role of antimicrobial peptides in the oral cavity.